Esterification of glycerol from biodiesel production to glycerol carbonate in non‑catalytic supercritical dimethyl carbonate - Ilham, Zul (Springer Open, 2016)
Conversion of glycerol from biodiesel production to glycerol carbonate was studied by esterification with dimethyl carbonate in a non-catalytic supercritical condition. It was found that in a non-catalytic supercritical condition, glycerol at higher purity gave higher yield of glycerol carbonate at 98 wt% after reaction at 300 °C/20–40 MPa/15 min. The yield of glycerol carbonate was observed to increase with molar ratio, temperature, pressure and time until a certain equilibrium limit. The existence of impurities such as water and remnants of alkaline catalyst in crude glycerol will direct the reaction to produce glycidol. Although impurities might not be desirable, the non-catalytic supercritical dimethyl carbonate could be an alternative method for conversion of glycerol from biodiesel production to value-added glycerol carbonate.